Regulatory CAR-T cells in autoimmune diseases: Progress and current challenges - Riet, Tobias; Chmielewski, Markus (Frontiers in Immunology, 2022)
CAR (Chimeric Antigen Receptor) T-cell therapy has revolutionized the field of oncology in recent years. This innovative shift in cancer treatment also provides the opportunity to improve therapies for many patients suffering from various autoimmune diseases. Recent studies have confirmed the therapeutic suppressive potential of regulatory T cells (Tregs) to modulate immune response in autoimmune diseases. However, the polyclonal character of regulatory T cells and their unknown TCR specificity impaired their therapeutic potency in clinical implementation. Genetical engineering of these immune modulating cells to express antigen-specific receptors and using them therapeutically is a logical step on the way to overcome present limitations of the Treg strategy for the treatment of autoimmune diseases. Encouraging preclinical studies successfully demonstrated immune modulating properties of CAR Tregs in various mouse models. Still, there are many concerns about targeted Treg therapies relating to CAR target selectivity, suppressive functions, phenotype stability and safety aspects. Here, we summarize recent developments in CAR design, Treg biology and future strategies and perspectives in CAR Treg immunotherapy aiming at clinical translation.